Ultralong purely organic aqueous phosphorescence supramolecular polymer for targeted tumor cell imaging - Zhou, Wei-Lei; Chen, Yong; Yu, Qilin; Zhang, Haoyang; Liu, Zhi-Xue; Dai, Xian-Yin; Li, Jing-Jing; Liu, Yu (Nature communications, 2020)
Purely organic room-temperature phosphorescence has attracted attention for bioimaging but can be quenched in aqueous systems. Here we report a water-soluble ultralong organic room-temperature phosphorescent supramolecular polymer by combining cucurbit[n]uril (CB[7], CB[8]) and hyaluronic acid (HA) as a tumor-targeting ligand conjugated to a 4-(4-bromophenyl)pyridin-1-ium bromide (BrBP) phosphor. The result shows that CB[7] mediated pseudorotaxane polymer CB[7]/HA–BrBP changes from small spherical aggregates to a linear array, whereas complexation with CB[8] results in biaxial pseudorotaxane polymer CB[8]/HA–BrBP which transforms to relatively large aggregates. Owing to the more stable 1:2 inclusion complex between CB[8] and BrBP and the multiple hydrogen bonds, this supramolecular polymer has ultralong purely organic RTP lifetime in water up to 4.33 ms with a quantum yield of 7.58%. Benefiting from the targeting property of HA, this supramolecular polymer is successfully applied for cancer cell targeted phosphorescence imaging of mitochondria. Room-temperature phosphorescence has attracted attention for bioimaging, but quenching in aqueous systems is an issue. Here, the authors report on the synthesis of a water soluble organic phosphorescent polymer and demonstrate application is cancer cell targeting and imaging.